Hip-Abductor Fatigue and Single-Leg Landing Mechanics in Women Athletes - Patrek, Mary F. (The National Athletic Trainers' Association, Inc, 2011)
CONTEXT: Reduced hip-abductor strength and muscle activation may be associated with altered lower extremity mechanics, which are thought to increase the risk for anterior cruciate ligament injury. However, experimental evidence supporting this relationship is limited. OBJECTIVE: To examine the changes in single-leg landing mechanics and gluteus medius recruitment that occur after a hip-abductor fatigue protocol. DESIGN: Descriptive laboratory study. PATIENTS OR OTHER PARTICIPANTS: Twenty physically active women (age  =  21.0 ± 1.3 years). INTERVENTION(S): Participants were tested before (prefatigue) and after (postfatigue) a hip-abductor fatigue protocol consisting of repetitive side-lying hip abduction. MAIN OUTCOME MEASURE(S): Outcome measures included sagittal-plane and frontal-plane hip and knee kinematics at initial contact and at 60 milliseconds after initial contact during 5 single-leg landings from a height of 40 cm. Peak hip and knee sagittal-plane and frontal-plane joint moments during this time interval were also analyzed. Measures of gluteus medius activation, including latency, peak amplitude, and integrated signal, were recorded. RESULTS: A small (<1°) increase in hip-abduction angle at initial contact and a small (<1°) decrease in knee-abduction (valgus) angle at 60 milliseconds after contact were observed in the postfatigue landing condition. No other kinematic changes were noted for the knee or hip at initial contact or at 60 milliseconds after initial contact. Peak external knee-adduction moment decreased 27% and peak hip adduction moment decreased 24% during the postfatigue landing condition. Gluteus medius activation was delayed after the protocol, but no difference in peak or integrated signal was seen during the landing trials. CONCLUSIONS: Changes observed during single-leg landings after hip-abductor fatigue were not generally considered unfavorable to the integrity of the anterior cruciate ligament. Further work may be justified to study the role of hip-abductor activation in protecting the knee during landing.